PENGARUH PRODUK DOMESTIK REGIONAL BRUTO DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL - Sari, Trisna Eka; Desvianti, Delia; Pakaya, Zulfikar (Relawan Jurnal Indonesia, 2023)
The capital expenditure of Bengkalis Regency fluctuates, this will disrupt the regional development process of Bengkalis Regency. This study aims to look at the effect of GRDP and Balance Fund on Capital Expenditure. The sampling technique used in this study is a census. The data used in this study are secondary data obtained from the Budget Realization Report and the Bengkalis Regency GRDP Report. Multiple Regression Analysis is used to see the effect of the independent variable on the dependent variable. The results showed that Gross Domestic Regional Product (GRDP) and Balance Fund partially had no effect on capital expenditure.